2017
DOI: 10.4103/jispcd.jispcd_149_17
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic consideration in implant-supported prosthesis: A review of literature

Abstract: Modern dentistry has changed tremendously with implant therapy. For the successful implant therapy, making a proper treatment plan considering both surgical and prosthetic part in mind is the key of success. Often practitioners tend to create a treatment plan overlooking the basic principles of prosthetic part. This present review has discussed various prosthetic consideration of implant-supported prosthesis. A step-by-step detailed prosthetic option with their indications has been discussed to help all dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The patients that did not fulfill the eligibility criteria, were excluded due to insufficient bone volume at implant sites and jaw shape. Bone volume has a substantial impact on available prosthetic options and should be a consideration in all treatment plans [23]. Our analysis showed that bone volume was a critical factor, leading more men than women to be eligible for this treatment concept.…”
Section: Discussionmentioning
confidence: 99%
“…The patients that did not fulfill the eligibility criteria, were excluded due to insufficient bone volume at implant sites and jaw shape. Bone volume has a substantial impact on available prosthetic options and should be a consideration in all treatment plans [23]. Our analysis showed that bone volume was a critical factor, leading more men than women to be eligible for this treatment concept.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy with cold physical plasmas shows beneficial effects in dermatology, [33,34] especially in wound healing. [10,35] With emergence of novel therapeutic applications and plasma source concepts, [36][37][38] there is an increasing need not only to show treatment efficacy but also to assess toxicological aspects. In this study, we aimed at investigating the suitability of zebrafish larvae as a toxicological model in plasma medicine.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Other authors recom mend the use of acrylic resin teeth for the fullarch prosthe ses restored over implants, since this type of material would compensate for the lack of resilience of this rehabilitation system, which is different from natural teeth, as natural teeth have periodontal ligaments. 10,11 In a finite element analysis study evaluating stress distri bution in the supporting structures with regard to materials of different hardness, the researchers showed that both resin types (composite and ceramicfilled resin) transmitted less load than porcelain or the gold alloy. 10 Other finite element analysis studies were unable to demonstrate benefits in stress distribution in the supporting structures with the use of more resilient materials.…”
Section: Introductionmentioning
confidence: 99%